Anterior ischemic optic neuropathy in a patient with erectile dysfunction: Tadalafil as an offending medication - Alireza Dehghani; Mohammad-Hasan Ale; Marjan Masjedi; Arman Amirkhani; Mohsen Pourazizi (Wolters Kluwer Medknow Publications, 2018)
Erectile dysfunction (ED) has negative effects on quality of life. The first line of oral medication for this condition is phosphodiesterase type 5 inhibitors (PDE5I) including Tadalafil. Ocular complications associated with Tadalafil are rare and usually occurred in participant with known risk factors. In this report, we describe and review the related literature of development of nonarteritic anterior ischemic optic neuropathy -associated Tadalafil. A healthy nonsmoking 42-year-old male with a history of ED presented with acute onset of an inferior visual field defect on the right eye. Automated perimetry showed inferior altitudinal loss in the affected eye. The administration of Tadalafil was discontinued as a potential causative agent for this condition. During follow-up, neither improvement signs nor symptoms revealed.